Allometric Biomass Equation Model of Sonneratia alba in Tanah Merah Mangrove Forest, Kupang, East Nusa Tenggara, Indonesia - Meilyn Renny Pathibang; Yudhistira A. N. R. Ora; Aah Ahmad Almuqu; Tristania Silvana Lalus; Sutan Sahala Muda Marpaung (Jurnal Penelitian Pendidikan IPA, 2026)
Mangrove forest biomass is an important parameter for carbon stock estimation and the sustainable management of coastal ecosystems. However, specific allometric equations for Sonneratia alba in mangrove forest ecosystems under semi arid environmental conditions characterized by relatively low rainfall, high salinity, and distinct muddy substrate characteristics remain limited. This study aims to develop a specific allometric equation model to estimate the biomass of Sonneratia alba in the Tanah Merah Mangrove Forest, East Nusa Tenggara. The method used to estimate biomass is destructive sampling and regression analysis. A total of fourteen sample trees representing seven diameter classes were harvested and measured for diameter at breast height (DBH), tree height, and biomass components. The collected data were analyzed to produce the best allometric equations relating tree dimensions to biomass. The results showed that the best equation for stem biomass was B = 0.036D^(2.503), branch biomass was B = 1.269e^(0.154D), leaf biomass was B = 0.000022D^(2.124)H^(2.621), and total biomass was B = 5.607e^(0.142D)). The estimated carbon stock potential of Sonneratia alba in the Tanah Merah Mangrove Forest was 8.64 tons ha⁻¹. These findings provide an important scientific basis for improving biomass and carbon stock estimation accuracy and support evidence-based mangrove conservation and management, particularly in coastal ecosystems of East Nusa Tenggara.